1991
DOI: 10.1007/bf02090169
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of low rectovaginal fistulas

Abstract: Forty women with low rectovaginal fistulas were operated upon over a 9-year period. The etiology of the fistula in the majority was obstetric. Nine women had prior attempts to repair the fistula. All 40 women were managed with endorectal advancement flap with the addition of sphincteroplasty or perineal body reconstruction in 15 patients and rectocele repair in six patients. Postoperative complications included urinary difficulties (two patients) and wound complications (three patients). There were two recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…Although some reports [2,6,7] have shown no improvements in the outcome of an advancement flap with a concomitant sphincteroplasty or puborectal sling interposition [8], other authors [10,13] clearly demonstrated the benefit of sphincteroplasty, especially in complex fistulas after previous failed repair or if a traumatic sphincter disruption is present [6,13]. In the present series, fistulectomy and sphincteroplasty was the most successful technique in the treatment of simple fistulas, but we also advocate the selection of that technique as the first option in the previously mentioned cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although some reports [2,6,7] have shown no improvements in the outcome of an advancement flap with a concomitant sphincteroplasty or puborectal sling interposition [8], other authors [10,13] clearly demonstrated the benefit of sphincteroplasty, especially in complex fistulas after previous failed repair or if a traumatic sphincter disruption is present [6,13]. In the present series, fistulectomy and sphincteroplasty was the most successful technique in the treatment of simple fistulas, but we also advocate the selection of that technique as the first option in the previously mentioned cases.…”
Section: Discussionmentioning
confidence: 97%
“…Results of endorectal advancement flap in the treatment of simple fistulas have been initially very good but it has been also demonstrated that the success rate drops with the number of previous procedures [2,6] and, more recently, several studies have reported a significantly lower healing rate [7][8][9][10]. The vaginal flap follows the same surgical principles as the rectal flap and shows no curative advantages over it, except in those cases were the rectal flap has already failed or it is not indicated due the anatomical or pathological conditions of the anorectum, as in patients with Crohn's disease or ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the Rockwood fecal incontinence severity index score before and after the procedure, no significant differences were found. After transanal advancement flap repair, impairment of fecal continence does occur in a substantial number of patients [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data it seems obvious that closure of the anal opening, by a transanal advancement flap repair, is not the only key to successful repair. Impairment of continence, observed in a substantial number of patients, is another drawback of this procedure [7,24]. In an attempt to improve the results, we added labial fat flap transposition to the advancement flap repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation